Estimation of growth in intact grazing Holstein steers (2013)
ABSTRACT: animal growth does not follow a linear pattern. Accordingly, fitted non-linear models are used to analyze the relationship between growth rate and age. Objective: to assess the ability of several mathematical models (Gompertz, Brody, and von Bertalanffy) to describe growth and development patterns of grazing Holstein males (Bos taurus). Methods: twenty eight intact Holstein steers (average weight 203.8 ± 37.5 kg) were used in the study. The animals grazed on Kikuyu grass pastures (Pennisetum clandestinum) and were supplemented with 1 kg dry matter of reconstituted grain silage until weight reached 301.9 ± 47.9 kg. Animals were weighed at the beginning of the experiment and monthly thereafter from 14 to 21 months of age. The Marquardt's iterative algorithm of PROC NLIN procedure for non-linear models available in the SAS software was used to fit the data to each model and estimate the parameters. Results: Brody model reached the highest estimated value for adult weight (1,097.6 kg) while the Gompertz model displayed the lowest value (795 kg). Bertalanffy model indicated the lowest estimate for maturity index (0.0028) while the highest estimate was obtained by Gompertz (0.0047), being statistically different (p < 0.05). Conclusions: Gompertz model best described growth of intact Holstein steers under rotational grazing and feed supplementation.